Notice of (1) Three Stone Cups found in a Cairn in Aberdeenshire, and (2) a Short Cist containing a Beaker Urn found at Boglehill Wood, Longniddry, East Lothian - Callander, J (Proceedings of the Society of Antiquaries of Scotland, 1916)
No record of the discovery of any sepulchral deposit within the cairn seems to have survived and the precise location of the cups is unclear. A circular cup of steatite or soapstone is decorated while a second is made of diorite and has the appearance of a ladle. The third cup was not available for examination. It is argued that the evidence for a Bronze Age date is inconclusive and the cups are more likely to be Iron Age in date. A short cist contained a fragmentary Beaker vessel and some charcoal. No human bone survived.